Present Scenario of Power Sector in India - Gakhar, Kamlesh; Meetu; Chaudhary, Niyati (Journal of Management and Science, 2013)
Infrastructure is a key requirement for the sustained growth of an economy. Within infrastructure, growth in the power sector is one of the most important requirements for such growth.Though, the installed generation capacity of Indian power sector increased over the years. Yet, the power sector lacked in quality, security and reliability. It was characterized by gross underinvestments, serious under recoveries and had the highest contribution to the India‘s fiscal deficit. In the wake of all these difficulties, it was necessary to bring reforms in this sector. The present paper is an attempt to describe the efforts taken by Indian government for the overhauling of this sector since 1991, gaps in its implication and the need for future reforms.